Development of a novel encystment medium: Enhancing diagnostic potential of Acanthamoeba spp. - Julalak Chuprom; Suthinee Sangkanu; Watcharapong Mitsuwan; Rachasak Boonhok; Alok K. Paul; Sonia M. Rodrigues Oliveira; Maria L. Pereira; Tajudeen O. Jimoh; Mohammed Rahmatullah; Polrat Wilairatana; Christophe Wiart; Ajoy K. Verma; et al. (Veterinary World)
Background and Aim: Acanthamoeba spp. are pathogenic microorganisms linked to severe infections in humans and animals, requiring a deeper understanding of their encystation process for effective diagnostics and research. This study focused on developing a novel encystment medium to induce synchronized encystation of Acanthamoeba spp. efficiently and rapidly.